2023
DOI: 10.1101/2023.04.19.537575
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired H19 lncRNA expression contributes to the compromised developmental angiogenesis in EVL-deficient mice

Abstract: Endothelial tip cells are essential for VEGF-induced angiogenesis, but underlying mechanisms are elusive. Endothelial-specific deletion of EVL, a member of the mammalian Ena/VASP protein family, reduced the expression of the tip cell marker protein endothelial cell specific molecule-1 (Esm1) and compromised the radial sprouting of the vascular plexus in the postnatal mouse retina. The latter effects could at least partly be attributed to reduced VEGF receptor 2 (VEGFR2) internalization and signaling but the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition to altered internalization of growth factor receptors, the Ena/VASP proteins may alter angiogenesis by other mechanisms. For example, a recent study reported that the expression of the long non-coding RNA H19 was significantly reduced in retinal endothelial cells from postnatal EVL −/− mice and in siRNA-transfected human endothelial cells under hypoxic conditions [220] (Figure 10B). Similar to EVL −/− mice, H19-deficient animals [224] displayed a significantly impaired radial sprouting of the vascular plexus on postnatal day 5 (Figure 10C,D), indicating that down-regulation of the lncRNA in EVL-deficient mice may contribute to the impaired angiogenic sprouting [220].…”
Section: Evl Regulates Vegf Receptor 2 Internalization and Signaling ...mentioning
confidence: 97%
See 2 more Smart Citations
“…In addition to altered internalization of growth factor receptors, the Ena/VASP proteins may alter angiogenesis by other mechanisms. For example, a recent study reported that the expression of the long non-coding RNA H19 was significantly reduced in retinal endothelial cells from postnatal EVL −/− mice and in siRNA-transfected human endothelial cells under hypoxic conditions [220] (Figure 10B). Similar to EVL −/− mice, H19-deficient animals [224] displayed a significantly impaired radial sprouting of the vascular plexus on postnatal day 5 (Figure 10C,D), indicating that down-regulation of the lncRNA in EVL-deficient mice may contribute to the impaired angiogenic sprouting [220].…”
Section: Evl Regulates Vegf Receptor 2 Internalization and Signaling ...mentioning
confidence: 97%
“…For example, a recent study reported that the expression of the long non-coding RNA H19 was significantly reduced in retinal endothelial cells from postnatal EVL −/− mice and in siRNA-transfected human endothelial cells under hypoxic conditions [ 220 ] ( Figure 10 B). Similar to EVL −/− mice, H19-deficient animals [ 224 ] displayed a significantly impaired radial sprouting of the vascular plexus on postnatal day 5 ( Figure 10 C,D), indicating that down-regulation of the lncRNA in EVL-deficient mice may contribute to the impaired angiogenic sprouting [ 220 ]. Consistent with this finding, knockdown of H19 in glioma-associated endothelial cells suppressed glioma induced angiogenesis [ 225 ].…”
Section: Evl Regulates Vegf Receptor 2 Internalization and Signaling ...mentioning
confidence: 99%
See 1 more Smart Citation